EKSISTENSI PIDANA MINIMUM KHUSUS SEBAGAI SARANA PENANGGULANGAN TINDAK PIDANA KORUPSI - Antonius Sudirman (Masalah-Masalah Hukum, 2015)
The essence of the  specific minimal criminal sanctions in the Anti-Corruption Act, as a means to prevent disparity in sentencing and as a deterrent effect for the corrupt. The formulation of a specific minimal criminal sanctions in the Anti-Corruption Act considered too small, so criminals are not afraid to do or repeat corruption. In the Anti-Corruption Act is not regulated on guidelines for the application of a specific minimal sentencing. Therefore, the Anti-Corruption Act needs to be reviewed with the aim to aggravate the minimal sentencing so can be a deterrent effect for the corrupt, and stipulate sentencing guidelines as a handle in the application of a minimal criminal sanctions.